(untitled) (Journal of Parents and Teachers, 2014)
In a devastated Russia by the revolution in 1917, young people were characterised by illiteracy and marginalisation close to delinquency. Makarenko defined education as the engine capable of transforming society and building a new society. As a result, Anton Semyonovich Makarenko established a new pedagogical model and defined a group of 500 individuals between the ages of 8 and 18. Some of the basic principles that were worked on in these communes were cooperation, participation and working together as essential elements.